PENGUATAN EKONOMI DAN SOSIAL MELALUI PROGRAM PENGABDIAN KEPADA MASYARAKAT: STUDI KASUS PADA MITRA SASARAN - Sabri Sabri; Mohamad Aras; Adnan Adnan; M. Arpah; Riswandhi Ismail (PUAN INDONESIA, 2026)
The main focus of this program is community empowerment, which is carried out systematically and sustainably. This empowerment is not only limited to knowledge transfer, but also includes coaching, mentoring, and evaluation that enable communities to be independent in the long term. Based on science, technology, and practical skills, PkM is designed to suit the specific needs of target partners. The technology introduced in this program must be able to be adopted and developed independently by the community, so that its benefits can continue even after the program has ended. Economic and social strengthening can be achieved through the Community Service (PkM) program by examining case studies of target partners. This analysis is conducted to understand the extent to which interventions provided through PkM are able to have a significant impact on improving community welfare. By exploring the various approaches that have been implemented in the PkM program, this article also aims to identify key factors that contribute to the program's success, as well as obstacles often encountered in its implementation.